Paragraph writing : - Zemach, Dorothy E (Macmilian, 2005)
Paragraph writing provides students with: focus on particular aspects of paragraph writing, such as topics, style, and development writing support to help them find, organize, and express their ideas language support to help them with vocabulary, grammar, and punctuation guidance on revewing their own and their classmates’ writing in order to make revisions structured, graded writing assignments at the end of each unit. Paragraph writing, for learners of American English, takes students from sentence formation to paragraph writing through a proves approach. This not only develops students’ paragraph writing skills, but also encourages them to become independent and creative writers. The back of the Student Book contains peer review forms and a grammar reference section. Paragraph writing leads naturally into COLLEGE WRITING. Paragraph writing: preparing students to make the grade.